Exchange Rates and Policy Choices: Some Lessons from Interdependence in a Multilateral Perspective - Koromzay, Val; Llewellyn, John; Potter, Stephen (American Economic Review, 1984)
Ten years of floating exchange rates have not resulted in national policy autonomy. Indeed, in today's world, it seems scarcely conceivable that any exchange rate regime could enable countries to achieve their domestic objectives independently of what is going on elsewhere in the world; interdependence of national economies simply may not permit independence of national policies. Does this mean that policies directed in each country at getting the domestic situation right are to some extent hostage to the policy choice of others? If so, how do the constraints manifest themselves? Are these constraints made more or less onerous by the way the works? These questions are addressed by this paper; it would be too much to suggest that they are answered, or, indeed, are answerable in any definitive way. The early optimism that floating would free countries from balance of payments constraints and thereby enable them to direct policy, particularly monetary policy, to domestic objectives is perhaps understandable. The conditions over the period to the late 1960's had in many respects been particularly favorable to exchange rate stability. It would be natural if this led to the view that the few cases where exchange rate adjustment seemed called for would be better handled if exchange rates were left free to float, so that adjustment could take place relatively early and smoothly. But it would now seem that the typical applied economist or policymaker inherited from the period both a personal data base and a model that left him ill-equipped, in a number of ways, for what was to follow. First, few could have foreseen the extent to which countering inflation would need to become the overriding objective of policy. Second, supply-side shocks became bigger and more numerous. Third, the freedom and volume of financial flows has increased enormously. Fourth, the system that had been provided for much of the Bretton Woods period by the nth country role and anti-inflationary policies of the United States was lost, and no new anchor put in place. It could well be that the regime of floating rates that has been in operation over the last ten years has, at least in its broad features, been the only one that could have functioned in the prevailing conditions. If so, it may be that the regime has, at times, had an unwarrantedly bad press. The regime, and arguments put forward for its adoption a decade ago, should be judged not against some hypothetical ideal standard, but rather against what might otherwise have taken place. Ten years on, this judgement is not easy to make: what has not worked well is clearer than what is needed to make things work better.